Collaborative Forest Management in Nepal: Stepping towards managing productive forests of Terai with social inclusion - Paudyal, Dhananjaya (The Initiation, 2010)
DOI: 10.3126/init.v1i0.2683 The Initiation Vol.1 2007 p.65-71